Mongolia Quarterly, January 2008 - World Bank (Washington, DC, 2017)
Real Gross Domestic Product (GDP) growth rate was 9.9 percent in 2007. Economic growth has been primarily driven by agriculture (which contributed 3.4 percentage points to economic growth), and services (which contributed 4.3 percentage points). In the agriculture sector, the December 2007 annual livestock census reported an increase of 15 percent of livestock from 34.8 to 40.3 mln livestock, with the number of goats, sheep and cattle increasing by 18, 15 and 14 percent respectively. While most of the foreign direct investment (FDI) coming into Mongolia continues to go to mining, its value-added only grew by only 1.7 percent this year (mainly came from coal extraction). On the non-bank side, the financial regulatory commission has been making efforts to improve the legal and regulatory framework, however, its weak institutional capacity and resource constraints continue to be a major impediment in effective supervision. Several key laws relating to the financial sector need to be finalized. Efforts have been made towards resolving immediate issues relating to the closed savings and credit cooperatives, developing the insurance industry and developing a framework and institutions to develop the mortgage market. However, several laws and enabling regulation still need to put in place before benefits of increase in financial sector efficiency (lower cost of financing) can be fully realized.